2013
DOI: 10.1016/j.ramb.2013.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Vitamina D: ações extraósseas e uso racional

Abstract: Recent years have witnessed a substantial increase in the number of seric determinations of vitamin D, in a worldwide basis. At Hospital das Clínicas of Faculdade de Medicina of Universidade de São Paulo that increase reached 700% over the last four years. Nevertheless there are many controversies on the literature about the role of vitamin D in conditions unrelated to the musculoskeletal system. In this study the metabolism, sources and actions of vitamin D on the body are reviewed. Observational studies, cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
30

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 49 publications
0
8
0
30
Order By: Relevance
“…Some studies have reported vitamin D deficiency to be a public health concern because of the growing number of people diagnosed with this deficiency and also because of the impacts of this deficiency on cancer, diabetes mellitus, depression, psychosis, cardiovascular disease, falls, muscle function, physical strength and hyperparathyroidism (23)(24)(25)(26)(27)(28) .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported vitamin D deficiency to be a public health concern because of the growing number of people diagnosed with this deficiency and also because of the impacts of this deficiency on cancer, diabetes mellitus, depression, psychosis, cardiovascular disease, falls, muscle function, physical strength and hyperparathyroidism (23)(24)(25)(26)(27)(28) .…”
Section: Discussionmentioning
confidence: 99%
“…Fontes endógenas de vitamina D permanecem duas vezes mais tempo no organismo que as exógenas. Entretanto, a vitamina D oriunda da exposição solar é influenciada por diversos fatores, como estação do ano, pigmentação da pele e uso de protetor solar, e a sua ingestão natural através da dieta, representa apenas uma pequena parte necessária para atender as necessidades humanas (5). Desta forma, na falta de uma exposição regular à luz do sol, apenas as fontes alimentares não são suficientes para manter níveis adequados e por isto a suplementação com medicamentos tem sido constantemente necessária (9).…”
Section: Introductionunclassified
“…However, in the last years, an important body of evidence has associated this metabolite with many extraskeletal outcomes, such as diabetes, cancer, and metabolic syndrome 6 . More recently, observational studies reported a relationship between vitamin D level and hemoglobin in many populations, especially in older adults [7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%